1995
DOI: 10.1557/jmr.1995.0640
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the reactive spreading of molten aluminum on ceramic surfaces

Abstract: The spreading kinetics of molten aluminum on ceramic surfaces bearing reactive coatings has been studied through the direct observation of sessile drops, either formed in situ or emplaced at temperature. Analysis of videotapes permitted the assessment of the rate of advance of rapidly spreading droplets. Experimental conditions in this study were chosen to avoid the severe retarding effect of the aluminum oxide film which is typically encountered in aluminum wetting experiments. A variety of reactive coating s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Coatings of nickel, silver, copper, and chromium have been applied to the surface of ceramics to enhance wettability, while the sodium process is used to prepare Al 2 O 3 for wetting by metallic liquids. [44][45][46][47][48][49][50][51][52][53] Chemical vapor deposition titanium coatings have been shown to enhance the wettability of alumina through the formation of intermetallic species at the ceramic surface. 54 Commercially available alloys include TiCuSil™ and InCuSil™.…”
Section: Improving Interfacial Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Coatings of nickel, silver, copper, and chromium have been applied to the surface of ceramics to enhance wettability, while the sodium process is used to prepare Al 2 O 3 for wetting by metallic liquids. [44][45][46][47][48][49][50][51][52][53] Chemical vapor deposition titanium coatings have been shown to enhance the wettability of alumina through the formation of intermetallic species at the ceramic surface. 54 Commercially available alloys include TiCuSil™ and InCuSil™.…”
Section: Improving Interfacial Propertiesmentioning
confidence: 99%
“…Additions of calcium, lithium, and magnesium improve the wettability of aluminum by reducing the oxide film, thus allowing intimate contact. 29,[47][48][49][50]57 The addition of oxygen and other surface-active elements to liquid metals has been shown to lower the solid-liquid, γ sl , and the liquid-vapor, γ lv , surface energies, thus improving wettability in certain instances. 58 This process is also known as direct bonding or gas-metal eutectic bonding.…”
Section: Improving Interfacial Propertiesmentioning
confidence: 99%
“…[22] Typically temperatures greater than 1000°C are necessary for Al to wet TiC and/or B 4 C preforms in MI experiments. [3,4] However, it has been previously reported that Ti additions to B 4 C porous preforms enhance the infiltration kinetics of Al into the latter, [3] which coincides with the finding that Ti-B interactions aid in the reactive wetting of Al on ceramic surfaces, [23] though the reaction mechanisms and phase equilibria remain largely un-investigated. [3] Nevertheless, this interest in manufacturing Al matrix composites with both borides and carbides [24] would be greatly aided by an understanding of the reaction mechanisms and especially the equilibrium phase relations of these systems.…”
Section: Introductionmentioning
confidence: 59%
“…Although the contact angle is higher with alumina-saturated bath compared with those obtained with low alumina fluxes, it is considerably lower than fluxless wetting in this range of temperatures. [1][2][3][4][5] Differences in the wetting and spreading of the TiB 2 substrate by molten aluminum at low temperatures in this work can be attributed to the ability of the flux to melt at a relatively low temperature and to its ability to dissolve the alumina skin on the droplet surface. The oxide film prevents the molten aluminum from achieving intimate contact with the ceramic, and its dissolution in the molten flux is vital to achieve wetting.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported in most cases that the wettability of TiB 2 by molten aluminum occurs well above the aluminum melting point. [1][2][3][4][5] For example, Rhee [2] obtained a contact angle of 57 deg after a 30-minute hold at 1107 K (834°C) under vacuum. Bardal et al [5] obtained a contact angle of 10 to 20 deg after a 100-minute hold at 1263 K (990°C) under vacuum.…”
Section: Introductionmentioning
confidence: 99%